Quantitative recovery of Burkholderia pseudomallei from soil in Thailand. - Smith, MD; Wuthiekanun, V; Walsh, A; White, N (1995)
Melioidosis is common in north-eastern Thailand, but is reported rarely from the adjacent areas of central Thailand, although rice farming is common to both regions. Quantitative soil cultures for Burkholderia pseudomallei were therefore prepared on 12 rice farms in both regions. B. pseudomallei was isolated from a similar proportion of rice fields in the central region (6/12) and in the north-east (7/12). Within the culture-positive sites, the number of B. pseudomallei colony-forming units (cfu) per mL of soil/water supernatant was significantly higher in the north-east (median 230 cfu/mL; range 1-17,000) than in the central region (median 10 cfu/mL; range 1-600). As bacterial counts in the soil are probably related to the risk of developing melioidosis, differences in exposure to B. pseudomallei probably contribute to the considerable differences in the incidence of this disease between these 2 adjacent regions.